Long-Term Results of Fixed High-Dose I-131 Treatment for Toxic Nodular Goiter: Higher Euthyroidism Rates in Geriatric Patients - DEDE, FUAT; TUROĞLU, HALİL TURGUT; İNANIR, SABAHAT; ERDİL, TANJU YUSUF (GALENOS YAYINCILIK, 2015)
Objective: Geriatric patient population has special importance due to particular challenges. In addition to the increase in incidence of toxic nodular goiter (TNG) with age, it has a high incidence in the regions of low-medium iodine intake such as in our country. The aim of this study was to evaluate the overall outcome of high fixed dose radioiodine (RAI) therapy, and investigate the particular differences in the geriatric patient population. Methods: One hundred and three TNG patients treated with high dose I-131 (370-740 MBq) were retrospectively reviewed. The baseline characteristics; age, gender, scintigraphic patterns and thyroid function tests before and after treatment, as well as follow-up, duration of antithyroid drug (ATD) medication and achievement of euthyroid or hypothyroid state were evaluated. The patient population was divided into two groups as those=>65 years and those who were younger, in order to assess the effect of age. Results: Treatment success was 90% with single dose RAI therapy. Hyperthyroidism was treated in 7 +/- 7, 2 months after RAI administration. At the end of the first year, overall hypothyroidism rate was 30% and euthyroid state was achieved in 70% of patients. Age was found to be the only statistically significant variable effecting outcome. A higher ratio of euthyroidism was achieved in the geriatric patient population. Conclusion: High fixed dose I-131 treatment should be preferred in geriatric TNG patients in order to treat persistent hyperthyroidism rapidly. The result of this study suggests that high fixed dose RAI therapy is a successful modality in treatni g TNG, and high rates of euthyroidism can be achieved in geriatric patients.
Keywords: Nodular goiter; I-131; geriatrics; hyperthyroidism